Toward Effects of Hydrophobicity on Biosurfactant Production by Bacillus subtilis Isolates from Crude-Oil-Exposed Environments - Seyedeh Zahra Hashemi; Jamshid Fooladi; Maliheh Vahidinasab; Philipp Hubel; Jens Pfannstiel; Evelina Pillai; Holger Hrenn; Rudolf Hausmann; Lars Lilge (Applied Microbiology, 2024)
Background: Due to their structural features, biosurfactants reveal promising physicochemical properties, making them interesting for various applications in different fields, such as the food, cosmetics, agriculture, and bioremediation sectors. In particular, the bioproduction of surfactin, one of the most potent microbially synthesized biosurfactant molecules, is of great interest. However, since the wild-type productivities are comparably low, stimulatory environmental conditions have to be identified for improved bioproduction This study aims to find a correlation between the hydrophobicity and production of the biosurfactant surfactin by B. subtilis isolates from crude-oil-contaminated soil and water. Methods: The surfactin production yield was characterized in adapted batch cultivations using high-performance thin-layer liquid chromatography (HPTLC). Defined hydrophobic environmental conditions were achieved by supplementation with hexadecane or polystyrene beads, and the effects on biosurfactant production were measured. Adaptations at the protein level were analyzed using mass spectrometry measurements. Results: The correlation between hydrophobicity and surfactin production was characterized using Bacillus subtilis strains ZH1 and P7 isolated from crude-oil-contaminated soil and water. Since these isolates show the biodegradation of crude oil and hexadecane as hydrophobic substrates, respectively, a first-time approach, using polystyrene beads, was applied to provide a hydrophobic environment. Interestingly, contrary to popular opinion, reduced biosurfactant production was determined. Using mass spectrometric approaches, the physiological effects of co-cultivation and the cellular response at the protein level were investigated, resulting in altered quantities of stress proteins and proteins involved in the carbon metabolism counter to polystyrene beads. Conclusions: Contrary to common opinion, increasing hydrophobicity does not have a stimulating effect, and even reduces the effect on the bioproduction of surfactin as the main biosurfactant using selected B. subtilis strains.